Genetic and environmental factors in the etiology of schizophrenia - towards mainstreaming - Łaba-Stefanek, Agnieszka; Dziwota, Ewelina; Olajossy, Marcin (Current Problems of Psychiatry, 2017)
The prevalence of schizophrenia in a population is about 1%. Many efforts are constantly made to find the cause of this mental illness. Authors of this article provide groups of factors influencing the development of the disease. Among these factors, genetics seems to be an interesting and reasonable trend of exploration. GWAS research studies allow not only determining the point mutations in the genome, but also try to give an answer to the question about the biological mechanisms of disease. A microRNA MIR137, which is involved in neurogenesis and maturation of neurons may be an example. However, the genetic component may not always be sufficient to trigger symptoms. Definitely, a large group of environmental factors has an important role. Schizophrenia is a complex disease in which many genes interact with the environment. This article is a presentation of genes and the impact of various external environmental factors, leading to the onset of schizophrenia. Interrelationship between polygenic determinant of disease and the impact of both environmental and social factors in future will certainly become the field of interest for research concerning the etiology and course of schizophrenia-spectrum disorders.